Loss of Lkb1 cooperates with BrafV600E and ultraviolet radiation, increasing melanoma multiplicity and neural‐like dedifferentiation - Kimberley McGrail; Elena González‐Sánchez; Paula Granado‐Martínez; Roberto Orsenigo; Yuxin Ding; Berta Ferrer; Javier Hernández‐Losa; Iván Ortega; Juan Martín‐Caballero; Eva Muñoz‐Couselo; Vicente García‐Patos; Juan A. Recio (Molecular Oncology)
The mechanisms that work alongside BRAFV600E oncogene in melanoma development, in addition to ultraviolet (UV) radiation (UVR), are of great interest. Analysis of human melanoma tumors [data from The Cancer Genome Atlas (TCGA)] revealed that 50% or more of the samples expressed no or low amounts of serine/threonine protein kinase STK11 (also known as LKB1) protein. Here, we report that, in a mouse model, concomitant neonatal BrafV600E activation and Lkb1 tumor suppressor ablation in melanocytes led to full melanoma development. A single postnatal dose of UVB radiation had no effect on melanoma onset in Lkb1‐depleted mice compared with BrafV600E‐irradiated mice, but increased tumor multiplicity. In concordance with these findings and previous reports, Lkb1‐null irradiated mice exhibited deficient DNA damage repair (DDR). Histologically, tumors lacking Lkb1 were enriched in neural‐like tumor morphology. Genetic profiling and gene set enrichment analyses of tumor sample mutated genes indicated that loss of Lkb1 promoted the selection of altered genes associated with neural differentiation processes. Thus, these results suggest that the loss of Lkb1 cooperates with BrafV600E and UVR, impairing the DDR and increasing melanoma multiplicity and neural‐like dedifferentiation.